Spatial variation in the gender and age composition of the population of Basra Governorate in 2022 - A’naad Ghayadh AL-Ogaily , Prof. Dr. Adnan (Basra studies journal, 2024)
The gender-age structure is one of the natural demographic characteristics that prevents human intervention and change. The gender structure divides the population into males and females, or into age groups that may be single, quintiles, or decimals for both sexes. This type of structure is considered an essential foundation in the study of population behavior represented by reproductive behavior, mortality, and migration, and the impact of these phenomena on changing the size of the population and its growth, in addition to its impact on community services, their variation, and the extent to which the population’s renewable needs are met. The research deals with the numbers of males and females at the governorate level and the variation in their gender ratio, as well as the reasons and factors influencing that variation at the governorate level. While the age structure specialized in studying the age groups for the broad and five-year categories and the reasons for their spatial variation at the governorate level, While the age structure specialized in studying the age groups for the broad and five-year categories and the reasons for their spatial variation at the governorate level, In addition to the indicators of age structure, which were the median age, the population pyramid, the dependency ratio, and the index of longevity, Which is considered a measure and criterion for knowing the stage that a population is going through (adolescence, youth, old age).